Status of refugees and international protection seekers: administrative-legal and socio-communicative aspects - Gerasymenko, Yevgen; Zadyraka, Nataliia; Georgiievska, Viktoria; Pohrebniak, Inha; Borets, Andrii (Jurnal Cita Hukum, 2025)
The article is aimed at disclosing the status of refugees and seekers of international protection: administrative, legal and socio-communicative aspects. It is proved that the content of the administrative and legal status of refugees includes the rights and freedoms that belong to them, which are classified into the following groups: non-specific rights, or basic universally recognized rights and freedoms, are enjoyed by non-citizens in the territory of the country of asylum (rights realized in the general order; rights with peculiarities of implementation in relation to refugees); specific rights (rights that belong only to refugees in the territory of the country of asylum, in particular, the right to monetary assistance, to preferential citizenship, to free legal assistance in cases of refugee status). It has been concluded that the administrative and legal status of refugees includes such individual specific duties established by the current legislation of Ukraine (for example, to notify the central executive body implementing the state policy in the field of refugees and persons in need of additional or temporary protection about their trips outside the administrative-territorial unit of Ukraine in whose territory they live).Keywords: status,  refugees, international protection, seekers, administrative-legal aspects, socio-communicative aspects, international standards, foreign experience.